2007
DOI: 10.1111/j.1600-0609.2007.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B1 is commonly expressed in the cytoplasm of primary human acute myelogenous leukemia cells and serves as a leukemia‐associated antigen associated with autoantibody response in a subset of patients

Abstract: Our studies demonstrate that primary human AML cells show aberrant cytoplasmic expression of cyclin B1 for a majority of patients and a specific humoral immune response was also detected for a subset of patients with untreated leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 63 publications
2
29
0
Order By: Relevance
“…Finally, the histone modifier MLL is affected by the various 11q23-involving translocations; MLL functions as a cell cycle regulator through its effects on CDC45 and the function of CDC45 in cell cycle regulation seems to be altered especially in the patient subset with these translocations [102]. Table 4 gives an overview of important regulators of the G2 phase that ends up with CDC25 mediated activation of CDK1/cyclin B; the described abnormalities of G2 regulation in primary human AML cells are summarized in the table [95,[127][128][129][134][135][136][137][138][139][140]. Similar to the G1 phase, the molecular context of CDC25 varies between patients also for this phase, but in contrast to the G1 phase where the heterogeneity is mainly due to the direct effects of AML-associated genetic abnormalities, the heterogeneity of G2 regulation is mainly determined by differences in expression levels (BRCA1, PP2A, PLK1, cyclin B) or isoform profiles (p53, PP2A).…”
Section: Regulation Of the S-phasementioning
confidence: 99%
“…Finally, the histone modifier MLL is affected by the various 11q23-involving translocations; MLL functions as a cell cycle regulator through its effects on CDC45 and the function of CDC45 in cell cycle regulation seems to be altered especially in the patient subset with these translocations [102]. Table 4 gives an overview of important regulators of the G2 phase that ends up with CDC25 mediated activation of CDK1/cyclin B; the described abnormalities of G2 regulation in primary human AML cells are summarized in the table [95,[127][128][129][134][135][136][137][138][139][140]. Similar to the G1 phase, the molecular context of CDC25 varies between patients also for this phase, but in contrast to the G1 phase where the heterogeneity is mainly due to the direct effects of AML-associated genetic abnormalities, the heterogeneity of G2 regulation is mainly determined by differences in expression levels (BRCA1, PP2A, PLK1, cyclin B) or isoform profiles (p53, PP2A).…”
Section: Regulation Of the S-phasementioning
confidence: 99%
“…42 The recently described AML-related CTA cyclin A1 has also been implicated in the G1/S-phase regulation. 33 Other LAAs, including AurA, 32 cyclin B1, 45 M-phase phosphoprotein 11 (MPP11), 36 NuSAP1, 46 SSX2IP 36 and RHAMM, 36 are predominantly involved in regulating the G2/M transition or the mitotic phase of the cell cycle. AurA, NuSAP1 and RHAMM are also required for mitotic spindle stability.…”
Section: Criterion 3: Oncogenicitymentioning
confidence: 99%
“…These studies, including WT1 peptide and WT1-targeted dendritic cell vaccine trials, have unequivocally established that CD8 þ T-cell immune responses specific to WT1 can be induced by active immunization in a substantial number of AML patients. 14 In those patients, multiple WT1 CTL epitopes have been recognized as immunogenic (including WT1 [37][38][39][40][41][42][43][44][45] , WT1 [126][127][128][129][130][131][132][133][134] , WT1 [187][188][189][190][191][192][193][194][195] and WT1 [235][236][237][238][239][240][241][242][243] ), demonstrating the excellent in vivo immunostimulatory potential of WT1 (Table 1). 14,72 This is further supported by the capacity to induce WT1-specific CD4 þ helper T-cell immunity in patients with AML through active immunization.…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the available data show that a number of the target antigens are cellular proteins, such as p53 whose aberrant regulation or overexpression is capable of leading to tumorigenesis, as well as CyclinB1 (Crawford et al, 1982;Winter et al, 1992;Soussi, 2000;Himoto et al, 2005;Ersvaer et al, 2007). It has been also demonstrated that the immune surveillance system in certain cancer patients has the capability of recognizing these antigenic changes in cancer cells and produce autoantibodies, which can amplify the response signal to the TAAs (Tan, 2001;Tan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%